PENINGKATAN PEMAHAMAN KONSEP MATA PELAJARAN MATEMATIKA MATERI NILAI TEMPAT PULUHAN DAN SATUAN MELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA PADA KELAS IB SD ISKANDAR SAID SURABAYA - Lailiyah, Nur (Journal Of Islamic Elementary School (JIES), 2018)
Indonesian Realistic Mathematics Education is an approach in learning mathematics not only showing the existence of a connection with the real world but rather refers to the focus of realistic in placing emphasis on the use of a situation that can be imaginable by students. From the results of the study, it can be concluded that the application of the Indonesian Realistic Mathematics Education approach in the IB class at Elemtary School Iskandar Said Surabaya can improve students' understanding of the concepts related to material place values ??of tens and units.